Variable Growth Across Species and Life Stages in Caribbean Reef Octocorals - Borgstein, Natascha; Beltrán, Diana M.; Prada, Carlos (Frontiers in Marine Science, 2020)
Growth rates often measured as linear extension rates can serve as a proxy for organismal performance across environments, yet few estimates of these growth rates exist, and fewer are reported from multi-year monitoring. We studied the effect of species, depth, exposure and life stages on the linear extension rates of common octocorals inhabiting Caribbean reefs. We monitored 16 species from the families Briareidae, Gorgoniidae, and Plexauridae, including eight genera: Antillogorgia, Briareum, Eunicea, Gorgonia, Muricea, Muriceopsis, Plexaura, and Plexaurella. We surveyed over 2,000 colonies across eight reefs in Southwest Puerto Rico from 2003 to 2006. Our surveys include reefs along a gradient of water motion from inside protected reefs to offshore unprotected reefs and from shallow (5 m) forereefs to deeper environments reaching 25 meters. We observed that linear extension rates vary across species and largely follow branch thickness variation and colony architecture, with thin plume-like shapes growing faster. We also found that in 7 out of the 16 species, colonies from shallow habitats with brighter and warmer environments have higher growth rates than colonies in deep, low energy, and darker areas. Importantly, small/juvenile corals of most species (< 10 cm) grew faster than adult colonies. Our data highlight the possibility that, as climate change continues to deteriorate Caribbean reefs by decimating scleractinian corals and opening new habitat for less vulnerable species, plume-like corals with fast growth rates such as species within the genus Antillogorgia may become the most abundant benthic cnidarians on Caribbean shallow forereefs.